Application of waqf for social and development finance - Salman Ahmed Shaikh; Abdul Ghafar Ismail; Muhammad Hakimi Mohd. Shafiai (ISRA International Journal of Islamic Finance, 2017)
Purpose: This paper aims to discuss the application of waqf (endowment) in the social finance sector for funding social and development projects and services. Design/methodology/approach The study is qualitative. It reviews literature and provides descriptive data to present its main idea. Findings Most Muslim-majority countries are generally income-poor, and the governments are generally weak in their tax collection, effective governance and capacity for development spending. Private sector financial institutions are scarce and mostly cater to the people who can meet the income-based lending criteria. Thus, the institution of waqf can fill the gap as a social finance institution by providing intermediation services for effectively utilising perpetual social savings. Flexibility in the rules of waqf enables it to serve beneficiaries directly or through financial institutions and to provide a wide range of social services. Research limitations/implications This conceptual research highlights the need and potential of waqf without discussing the regulatory and operational details of how to effectively institutionalize it in different regions. Practical implications The institution of waqf can harness the potential of selfless charitable giving in an effective way for better economic impact in the targeted social segments of society. Originality value The paper suggests the establishment of waqf-based training and vocational centres which will increase opportunities of self-employment and contribute in upward social mobility of beneficiaries.
Keywords: 330; Charitable giving; Selfless behaviour; Waqf